Perlindungan Hukum Pemegang Hak Desain Industri Berbasis Artificial Intelligence di Indonesia Berdasarkan Undang-Undang Desain Industri - Niswah, Eva Mir'atun (Universitas Muhammadiyah Kotabumi, 2025)
The development of artificial intelligence (AI) has introduced a new approach in the process of producing industrial designs. However, the use of AI in industrial design poses challenges in the protection of Intellectual Property Rights, especially regarding ownership and exclusive rights to industrial designs produced by AI. This article aims to discuss the legal framework for the protection of industrial designs produced by AI in Indonesia based on Law No. 31 of 2000 concerning Industrial Design (Undang-Undang Desain Industri/UUDI), and to analyze the challenges faced in the protection of AI-based industrial designs. The method used is empirical juridical, with a statue approach. Based on the results of the analysis, the legal status of the holder of Industrial Design Rights produced by AI according to UUDI remains with humans, AI can be personified as a relationship between workers and employers, then equated with objects in this case animals whose responsibility lies with their owners, and as partial legal subjects such as children in this case AI is always under guardianship. Then, the legal challenges in the protection of AI-based industrial designs, including regarding ownership and industrial design rights by AI, issues of novelty and originality and regulations that are not yet adaptive to technology.